VOCATIONAL EDUCATION CURRICULUM DEVELOPMENT POLICY COMPETENCY-BASED AT INSTITUTE OF HOME AFFAIRS GOVERNANCE - Eskandar, Eskandar (Jurnal Kebijakan Pemerintahan, 2024)
Abstract Institute of Home Affairs Governance (IPDN) plays a crucial role in producing competent graduates as Civil Servants (ASN), prepared to enhance public services and governance. However, IPDN’s curriculum is often criticized for being overly generic and insufficiently responsive to the diverse conditions encountered across various regions in Indonesia. As a result, IPDN graduates often struggle to deliver solutions that align with the specific needs of regions, resulting in suboptimal contributions to regional development. This policy paper aims to identify the underlying issues in the formulation of competency-based vocational education curriculum policies at IPDN. The research employed a descriptive, qualitative approach, with data collected through interviews, documentation, and literature studies. The findings indicate that the development of a competency-based vocational education curriculum at IPDN incorporates the integration of digital technology and e-government systems. Soft skills, along with problem-based learning and projects, will increasingly align with contemporary needs, resulting in graduates who possess not only technical competence but also digital skills, leadership abilities, and critical and innovative thinking for effective problem-solving. The proposed policy recommendations include the immediate formation of a curriculum design team by IPDN’s Rector to integrate digital technology and e-government into the learning framework; the development of specialized modules aimed at enhancing communication skills, ethics, collaboration, and leadership; and the design of a curriculum that incorporates real-world challenges encountered by central and regional governments as educational materials. Keywords: Leadership, Learning, Curriculum Development, Vocational Education, Digital Technology